1990
DOI: 10.1021/bi00454a020
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of Escherichia coli cystathionine .gamma.-synthase: direct evidence for a pyridoxamine derivative of vinylgloxylate as a key intermediate in pyridoxal phosphate dependent .gamma.-elimination and .gamma.-replacement reactions

Abstract: Cystathionine gamma-synthase catalyzes a pyridoxal phosphate dependent synthesis of cystathionine from O-succinyl-L-homoserine (OSHS) and L-cysteine via a gamma-replacement reaction. In the absence of L-cysteine, OSHS undergoes an enzyme-catalyzed, gamma-elimination reaction to form succinate, alpha-ketobutyrate, and ammonia. Since elimination of the gamma-substituent is necessary for both reactions, it is reasonable to assume that the replacement and elimination reaction pathways diverge from a common interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 14 publications
2
92
0
1
Order By: Relevance
“…Certain synthases, e.g. tryptophan synthase (Ahmed et al, 1986) and 0-succinylhomoserine (thio1)-lyase (BrzoviC et al, 1990), have been reported to catalyze in the absence of the replacing substrate the corresponding elimination reaction instead of the replacement reaction. The above side reactions correspond to the regio-specificity for the principal reaction except in the case of tryptophan synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Certain synthases, e.g. tryptophan synthase (Ahmed et al, 1986) and 0-succinylhomoserine (thio1)-lyase (BrzoviC et al, 1990), have been reported to catalyze in the absence of the replacing substrate the corresponding elimination reaction instead of the replacement reaction. The above side reactions correspond to the regio-specificity for the principal reaction except in the case of tryptophan synthase.…”
Section: Discussionmentioning
confidence: 99%
“…The high resolution crystal structures of Escherichia coli CBL (4) and CGS (5), together with crystallographic (6) and kinetic investigations (6 -9) on inhibitors, allowed the suggestion and evaluation of reaction mechanisms (4,10). Both CBL and CGS are homotetramers composed of ϳ40 -45-kDa subunits and carry one PLP cofactor per monomer covalently bound via a Schiff base to an active site lysine.…”
mentioning
confidence: 99%
“…At the resolution of our structure, we do not exclude a saturation of the N-CA bond, but the geometry of the complex is more compatible with the double N-CA bond. For mechanisms of ␥-elimination and ␥-replacement reactions catalyzed by PLP-dependent enzymes, it was postulated that ketimine (Scheme 1, V) is a plausible intermediate for effective labilization of the C␤-proton to proceed (17). Its formation in the course of these reactions catalyzed by E. coli cystathionine ␥-synthase was detected by stopped-flow data in the same paper.…”
Section: Inhibition Of ␥-Eliminationmentioning
confidence: 86%
“…The enzyme is also able to catalyze the ␤-elimination reaction of L-cysteine and the S-substituted L-cysteines (Reaction 2) and the ␥-and ␤-replacement reactions of L-methionine and L-cysteine and their analogs (15,16). The chemical mechanism (Scheme 1) of ␥-elimination reaction was proposed by Brzovic et al (17).…”
mentioning
confidence: 97%